An investigation into the roles played by interleukin-1Beta and reactive oxygen species in the rat brain during ageing - Martin, Darren (Trinity College (Dublin, Ireland). Department of Physiology, 2002)
Ageing is associated with an increase in reactive oxygen species production and an increase in the concentration of the pro-inflammatory cytokine interleukin-1β in the hippocampus. These have both been shown to have deleterious effects on the brain and specifically on a model of learning and memory, long-term potentiation. The ability of aged animals to m aintain LTP is impaired and it is postulated that the increases in ROS accumulation and IL-1β concentration may affect one factor which contributes to the expression of LTP in perforant path granule cell synapses, glutamate release. It has been shown that dietary manipulation with antioxidants or essential fatty acids reverses some of the age-related changes observed in the rat brain. In the present study, the ability of the antioxidants, a-lipoic acid and vitamins E and C , and the polyunsaturated fatty acid, eicospentanoic acid, in reversing certain age-related changes in the hippocampus and cortex was assessed.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin